Pregnancy Preparation Analysis And Determinant Factors In Pregnant Women - Nuriah Arma; Harmy bin Mohamed Yusoff; Hassan Basri bin Mukhali (Jurnal Kebidanan dan Kesehatan Tradisional, 2022)
Background: Pregnancy preparation is still not the focus of attention for pregnant women. Good pregnancy preparation is supported by three factors, namely social demographics, pregnancy characteristics, and a history of depression. This study aims to analyze pregnancy preparation and its determinant factors in pregnant women in Medan City, North Sumatra Province. Methods: This research is quantitative correlational analytic research with a cross-sectional approach. The population in this study was all pregnant women at health centers in Medan City, North Sumatra. The sampling technique used simple random sampling, with a total of 375 pregnant women. The data were analyzed through the Chi-Square test. Results: There was a significant relationship between age ( p = 0.005), education (p = 0.001), economic status (p = 0.012), pregnancy status  (p = 0.000), and history of depression (p = 0.002) with preparation for pregnancy in pregnant women.  Conclusion: The existence of socio-demographic relationships, pregnancy characteristics, and a history of depression with pregnancy preparation in pregnant women provide an overview for health workers to assist in pregnancy preparation during preconception.